2014
DOI: 10.1007/s10147-014-0703-5
|View full text |Cite
|
Sign up to set email alerts
|

Administration of chemotherapy via the median cubital vein without implantable central venous access ports: port-free chemotherapy for metastatic colorectal cancer patients

Abstract: Port-free-chemotherapy administration via the median cubital vein is appropriate for patients with colorectal cancer, thereby avoiding complications associated with CV-ports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…We previously reported port-free chemotherapy administration via the median cubital vein for CRC and showed that the resulting low complication rates helped to ensure completion of chemotherapy without delay for most patients (Yoshida et al 2012, b). However, VP occasionally necessitates changing an oxaliplatin drip infusion to a peripheral vein during XELOX therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported port-free chemotherapy administration via the median cubital vein for CRC and showed that the resulting low complication rates helped to ensure completion of chemotherapy without delay for most patients (Yoshida et al 2012, b). However, VP occasionally necessitates changing an oxaliplatin drip infusion to a peripheral vein during XELOX therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 58 patients with metastatic CRC who underwent XELOX plus bevacizumab therapy (7.5 mg/kg bevacizumab and 130 mg/m 2 oxaliplatin on day 1 plus 2000 mg/m 2 capecitabine on days 1–14, repeated every 3 weeks) or XELOX therapy (130 mg/m 2 oxaliplatin on day 1 plus 2000 mg/m 2 capecitabine on days 1–14, repeated every 3 weeks) (Yoshida et al 2015a, b) at Fukuoka University Hospital between April and August 2014 were included in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…KRAS codon 12 showed TGT mutation. We started XELOX + bevacizumab therapy (BV [7.5 mg/kg] and oxaliplatin [130 mg/m 2 ] on day 1 plus capecitabine [1,000 mg/m 2 ] twice daily on days 1–14, every 3 weeks) as a first-line treatment [3] and then started IRIS + bevacizumab therapy (BV [7.5 mg/kg] and irinotecan [150 mg/m 2 ] on day 1 plus S-1 [80 mg/m 2 ] twice daily on days 1–14, every 3 weeks) as a second-line treatment [4]. Prior to chemotherapy, the renal, hepatic, and bone marrow functions were almost normal.…”
Section: Case Reportmentioning
confidence: 99%
“…Patients underwent XELOX therapy (130 mg/m 2 oxaliplatin on day 1+1000 mg/m 2 capecitabine twice daily on days 1‐14) on postoperative day 7 and XELOX+bevacizumab (7.5 mg/kg bevacizumab and 130 mg/m 2 oxaliplatin on day 1+1000 mg/m 2 capecitabine twice daily on days 1‐14, every 3 weeks) after the second chemotherapy cycle 13, 14. Dose reductions were required for all grade 3 or 4 toxicities that were attributed to the study medications.…”
Section: Methodsmentioning
confidence: 99%